Online Shopping Addiction dalam Perspektif Islam Maslahah - Puput Winarsih; Ilham Mundzir (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The rapid development of information technology has changed consumer behavior, especially when it comes to online shopping. Ease of access to information and transactions via the internet has created a new phenomenon, namely online shopping addiction (OSA). OSA is defined as the tendency to shop excessively and compulsively over the internet, which can cause economic, social, and emotional problems. Research shows a positive correlation between internet addiction and online shopping addiction. Although online shopping provides convenience, it can also have negative impacts such as compulsive buying and financial problems. OSA can be measured along six dimensions: salience, mood modification, tolerance, withdrawal, conflict, and relapse. Individual coping skills play an important role in overcoming compulsive shopping tendencies. Individuals with good active coping skills tend to be better able to manage situational demands and have a lower risk of developing addictive behaviors such as OSA. Understanding OSA and the factors that influence it is important for developing effective prevention and intervention strategies in overcoming the problem of online shopping addiction in this digital era.